The impact of misinformation in social media that caused panic behavior on COVID-19 pandemic among university students in Ipoh, Perak / Kevin Wang Zi Xu ... [et al.] - Xu, Kevin Wang Zi; Mohd Pahme, Nur Faizah; Mohd Shuib, Ahmad Sofiyuddin; Abdullah, Anwar Fikri; Soedewi, Sri (Universiti Teknologi MARA, Perak, 2023)
Social networking has become a regular part of everyone's life. Nowadays, practically everyone uses social media and messaging platforms for communication, especially university students who frequently use smartphones and other devices for social interaction and communication. Due to this, university students began to believe the information shared on social media without verifying its accuracy. The veracity of the information shared on social media is unconfirmed for a number of reasons. Some of the false information spread has led to students at the university behaving panicked. As a result, the focus of this study will be on the effect of misleading news on Covid-19 among Malaysian university students. This will help to ensure that the study's goals, which include determining how social media misinformation influences university students' behaviour and fostering the spread of fear about COVID-19 in Malaysia, are successfully attained. In due to that the study uses quantitative methodology as its main research approach. Information was gathered by the researcher from university students using online surveys. The findings of this study indicated that disinformation disseminated via social media platforms, particularly the amplifying of dread that resulted in increased worry and anxiety, was likely to have an impact on university students in Ipoh, Perak. In order to discover the trends that may spread to other new consumers, particularly with the increased adoption of mobile connectivity, this study should be continued by focusing on the behavioural patterns and attitudes of this news consumption segment.